THE ROLE OF INTERNATIONAL FESTIVALS IN SHAPING THE AESTHETIC TASTE OF YOUTH (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article analyses the role and significance of international festivals in shaping the aesthetic taste of young people. From this perspective, international festivals are examined as an effective creative process that fosters the development of youth’s artistic thinking, aesthetic perception, tolerance, and cultural identity. Such events serve as a dynamic platform for intercultural dialogue and creative exchange, contributing to the spiritual and aesthetic growth of the younger generation.